PENGARUH KEPEMIMPINAN, KOMPETISI, GANJARAN DAN MOTIVASI KERJA TERHADAP EFEKTIVITAS ORGANISASI, BADAN PEMERIKSA KEUANGAN (BPK RI) JAKARTA - Nuraida Hidayati (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2017)
This causal research is aimed at obtaining information related to the effect of leadership,competition, rewards and motivation to work on the effectiveness of organization.In this research, 70 samples were selected randomly and the data has been analysed by pathanalysis after all variables put into the correlation matrix.The finding of the research shows that effectiveness of organization is affected directly andindirectly by leadership, competition, rewards and motivation to work.Based on those findings, it can be concluded that any changes or variations which occured at theeffectiveness of organization are affected by leadership, competition, rewards and motivation to work.Therefore, in increasing the effectiveness of organization, leadership, competition, rewards andmotivation to work should be put into strategic planning of human resources in the Indonesian AuditSupreme Board Jakarta (BPK RI Jakarta); however other variables are necessary to be taken intoaccount by the next research.